Ministry Of Manpower And Immigration Decree No. 372 Of The Year 2013 Concerning Disposition Of The Proceeds Of The Pecuniary Sanctions Inflicted On The Workers = وزارة القوى العاملة والهجرة قرار رقم 372 لسنة 2013 بشأن التصرف فى حصيلة اموال الجزاءات المالية الموقعة على العمال - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.